Automated detection and classification of liver fibrosis stages using contourlet transform and nonlinear features. (November 2018) - Acharya, U Rajendra; Raghavendra, U; Koh, Joel E W; Meiburger, Kristen M; Ciaccio, Edward J; Hagiwara, Yuki; Molinari, Filippo; Leong, Wai Ling; Vijayananthan, Anushya; Yaakup, Nur Adura; Fabell, Mohd Kamil Bin Mohd; Yeong, Chai Hong
Highlights: Our proposed system classifies different stages of liver fibrosis using ultrasound images. Two-dimensional contourlet transform and texture features are efficiently extracted. The analysis of variance-based feature ranking technique is used. The system achieved 91.46% accuracy with only four features using a probabilistic neural network classifier. Abstract: Background and objective: Liver fibrosis is a type of chronic liver injury that is characterized by an excessive deposition of extracellular matrix protein. Early detection of liver fibrosis may prevent further growth toward liver cirrhosis and hepatocellular carcinoma. In the past, the only method to assess liver fibrosis was through biopsy, but this examination is invasive, expensive, prone to sampling errors, and may cause complications such as bleeding. Ultrasound-based elastography is a promising tool to measure tissue elasticity in real time; however, this technology requires an upgrade of the ultrasound system and software. In this study, a novel computer-aided diagnosis tool is proposed to automatically detect and classify the various stages of liver fibrosis based upon conventional B-mode ultrasound images. Methods: The proposed method uses a 2D contourlet transform and a set of texture features that are efficiently extracted from the transformed image. Then, the combination of a kernel discriminant analysis (KDA)-based feature reduction technique and analysis of variance (ANOVA)-based feature ranking technique was used, and the images were then classified into various stages of liver fibrosis. Results: Our 2D contourlet transform and texture feature analysis approach achieved a 91.46% accuracy using only four features input to the probabilistic neural network classifier, to classify the five stages of liver fibrosis. It also achieved a 92.16% sensitivity and 88.92% specificity for the same model. The evaluation was done on a database of 762 ultrasound images belonging to five different stages of liver fibrosis. Conclusions: The findings suggest that the proposed method can be useful to automatically detect and classify liver fibrosis, which would greatly assist clinicians in making an accurate diagnosis.